2018
DOI: 10.3390/agriculture8030032
|View full text |Cite
|
Sign up to set email alerts
|

Limits to the Biofortification of Leafy Brassicas with Zinc

Abstract: Many humans lack sufficient zinc (Zn) in their diet for their wellbeing and increasing Zn concentrations in edible produce (biofortification) can mitigate this. Recent efforts have focused on biofortifying staple crops. However, greater Zn concentrations can be achieved in leafy vegetables than in fruits, seeds, or tubers. Brassicas, such as cabbage and broccoli, are widely consumed and might provide an additional means to increase dietary Zn intake. Zinc concentrations in brassicas are limited primarily by Zn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…It is considered the most economical solution for micronutrient deficiency in humans and animals [14]. Several studies have shown that Zn fertilization is efficient at increasing the Zn concentration in foods [13,15,16]. Yet, leafy vegetables are more suitable for achieving higher Zn concentrations than fruits, tubers, or seeds, since Zn is mainly transported through the xylem of plants [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…It is considered the most economical solution for micronutrient deficiency in humans and animals [14]. Several studies have shown that Zn fertilization is efficient at increasing the Zn concentration in foods [13,15,16]. Yet, leafy vegetables are more suitable for achieving higher Zn concentrations than fruits, tubers, or seeds, since Zn is mainly transported through the xylem of plants [8,17].…”
Section: Introductionmentioning
confidence: 99%
“…Low zinc contents in plant products are a serious issue for human nutrition, and may cause zinc deficiency for a large percentage of the worldwide population [16,23]. Biofortification was, in the past, mainly investigated in staple crops (e.g., wheat, potato).…”
Section: Nutrient Redistribution Within Plants and Accumulation In Hamentioning
confidence: 99%
“…Such transport processes and their regulation allow an accumulation of nutrients in harvested vegetative [16] or reproductive plant parts [17,18]. The mobility of an element or of certain forms of an element in the phloem is crucial for redistribution processes within the plant [13,19,20].…”
Section: Nutrient Redistribution Within Plants and Accumulation In Hamentioning
confidence: 99%
See 2 more Smart Citations